2022
DOI: 10.1108/ijopm-05-2022-0282
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of knowledge management processes in the effective use of artificial intelligence in manufacturing firms

Abstract: PurposeThis paper aims to provide and empirically test a conceptual model in which artificial intelligence (AI), knowledge management processes (KMPs) and supply chain resilience (SCR) are simultaneously considered in terms of their reciprocal relationships and impact on manufacturing firm performance (MFP).Design/methodology/approachIn the study, six hypotheses have been developed and tested through an empirical survey administered to 120 senior executives of Italian manufacturing firms. The data analysis has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 130 publications
1
18
0
Order By: Relevance
“…Similarly, Bhatti et al (2021) asserted that KMC synchronised internal and external knowledge flows to support firms' innovation adoption and collaborative strategies in Pakistani firms. Moreover, recent research has also endorsed the critical effect of firms' knowledge capabilities on supply chain transformation initiatives (Irfan et al, 2022;Leoni et al, 2022;Ngo et al, 2022;Pizzichini et al, 2023). The present study, drawing on the previously mentioned argument, hypothesised that: H6.…”
Section: Kmc and Dscmentioning
confidence: 53%
“…Similarly, Bhatti et al (2021) asserted that KMC synchronised internal and external knowledge flows to support firms' innovation adoption and collaborative strategies in Pakistani firms. Moreover, recent research has also endorsed the critical effect of firms' knowledge capabilities on supply chain transformation initiatives (Irfan et al, 2022;Leoni et al, 2022;Ngo et al, 2022;Pizzichini et al, 2023). The present study, drawing on the previously mentioned argument, hypothesised that: H6.…”
Section: Kmc and Dscmentioning
confidence: 53%
“…Finally, despite others having already combined the lens of IPT and knowledge-based view (Herden, 2020;Song et al, 2005), or knowledge based view and disruption management (Kwak et al, 2018;Leoni et al, 2022;Scholten et al, 2019), this study offers new and valuable insights to those theories and for the supply chain disruption management field revealing how contingent factors like COVID-19 could influence the effectiveness of knowledge created, stored and retrieved by means of digital technologies in building more resilient and robust supply chains. The results demonstrated that the impact of memory on robustness is negatively moderated by the COVID-19 impact on the supply chains, i.e.…”
Section: Contributions To Theory and Practicementioning
confidence: 94%
“…AI includes the corpus of knowledge allowing machines to behave in intelligent human-like manners (Bawack et al, 2021); hence, AI can generate positive impacts on the agility, resilience and performance of a supply chain (Dubey et al, 2022). It is therefore imperative to incorporate the artificial knowledge management concept within the study of resilience in SCM (Leoni et al, 2022). However, the resilience perspective of artificial knowledge remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…, 2022). It is therefore imperative to incorporate the artificial knowledge management concept within the study of resilience in SCM (Leoni et al. , 2022).…”
Section: Introductionmentioning
confidence: 99%